Alternative-fuel-vehicle policy interactions increase U.S. greenhouse gas emissions. (June 2019) - Jenn, Alan; Azevedo, Inês L.; Michalek, Jeremy J.
Abstract: The transportation sector is currently the largest contributor of greenhouse gas (GHG) emissions in the United States, and light-duty vehicles produce the majority of transportation emissions. Federal standards for fleet-averaged vehicle GHG emission rates and their corresponding corporate average fuel economy standards cap GHG emissions of the US light-duty vehicle fleet. In addition, two key policies aim to encourage a future fleet transition to alternative fuel vehicle (AFV) technologies: (1) incentives that treat AFVs favorably in the federal GHG standard, and (2) state zero-emissions vehicle (ZEV) policy, which mandates AFV sales in some states. While each of these AFV policies can encourage AFV adoption, we show that net GHG emissions increase when both policies are present simultaneously. Specifically, we estimate changes in life cycle GHG emissions and gasoline consumption, relative to a pure federal fleet GHG standard (without AFV incentives or mandates), resulting from the introduction of (1) AFV incentives in federal fleet GHG policy, (2) state ZEV mandates, and (3) the combination of the two. We find that under fairly general conditions the combined AFV policies produce higher GHG emissions than either policy alone. This result is a consequence of state mandates increasing AFV sales in the presence of federal incentives that relax the fleet GHG standard when AFVs are sold. Using AFV sales projections from the Energy Information Administration and the California Air Resources Board, we estimate that the combined policies produce an increase on the order of 100 million tons of CO2 emissions cumulatively for new passenger cars sold from 2012 through 2025 relative to a pure GHG standard. AFV incentives in the GHG standard conflate policy goals by encouraging AFV adoption at the cost of higher fleet GHG emissions, and they permit even higher fleet GHG emissions when other policies, such as the ZEV mandate, increase AFV adoption.